2021
DOI: 10.3389/fgwh.2021.757706
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Symptom Monitoring on Menopausal Health Outcomes: A Systematic Review and Meta-Analysis

Abstract: Evidence suggests that monitoring and appraising symptoms can result in increased engagement in medical help-seeking, improved patient-doctor communication, and reductions in symptom prevalence and severity. To date, no systematic reviews have investigated whether symptom monitoring could be a useful intervention for menopausal women. This review explored whether symptom monitoring could improve menopausal symptoms and facilitate health-related behaviours. Results suggested that symptom monitoring was related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
3
7
1
Order By: Relevance
“…The present study suggested that health-related behaviors, such as health communication, self-efficacy, decision making, and help-seeking intentions, were not influenced by symptom monitoring. This finding contrasts with results from Andrews et al 1 who demonstrated that symptom monitoring could lead to improvements in these behaviors. One reason for this outcome could be due to the 2-week research period used by the present study, which may not have been enough to time to alter health-related behaviors.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The present study suggested that health-related behaviors, such as health communication, self-efficacy, decision making, and help-seeking intentions, were not influenced by symptom monitoring. This finding contrasts with results from Andrews et al 1 who demonstrated that symptom monitoring could lead to improvements in these behaviors. One reason for this outcome could be due to the 2-week research period used by the present study, which may not have been enough to time to alter health-related behaviors.…”
Section: Discussioncontrasting
confidence: 95%
“…The result that symptom monitoring reduced physical symptoms is supportive of previous findings. The systematic review conducted by Andrews et al 1 demonstrated that using symptom diaries had a large effect on reducing hot flush frequency scores via meta-analyses, and qualitative findings suggested that symptom diaries could improve symptoms relating to depression, headaches, and urinary incontinence. Supporting these outcomes, the present study indicated that night sweats and headaches were positively influenced by the symptom monitoring intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings remained significant after controlling for covariates such as HRT use, hormonal contraceptive use, supplement use, age, and current comorbidities. These findings are in line with prior research in the field of female health which has demonstrated that symptom monitoring during menopause and use of digital health apps which enable period logging and digital health promoting activities are associated with health improvements (5,6,3,4).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the total number of days spent monitoring symptoms independently predicted symptom reductions. This is in-line with prior research which has demonstrated that symptom monitoring can result in reductions in menopausal symptoms (5,6). However, combined weekly engagement with the app was associated with greater reductions in symptoms than symptom monitoring alone, suggesting that using multiple facets of the Health & Her app can bestow greater benefits to the user.…”
Section: Discussionsupporting
confidence: 88%